Pengembangan Wisata dengan Metode Identifikasi 4a (Attraction, Amenity, Accesibility dan Ancilliary) di Desa Matajang - Muhlis, Muhlis; Asfar, Andi Muhammad Irfan Taufan; Nurannisa, Andi; Asfar, Andi Muhamad Iqbal Akbar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The issues of inadequate tourism management and the community's limited knowledge and understanding of tourism potential have become significant challenges in various regions, including Matajang Village. Insufficient management capacity has resulted in poorly maintained facilities and infrastructure, further aggravated by the COVID-19 pandemic, which led to a sharp decline in visitor numbers. Consequently, many previously thriving tourism sites in 2020 have been abandoned. This community service program (PKM) aims to address these challenges by providing education and skills enhancement to the local community through the 4A method (Attraction, Amenity, Accessibility, and Ancillary). The program seeks to foster partner independence in revitalizing and developing Baruttung Natural Bathing tourism using the 4A framework. The community service is conducted in three phases: counseling, training, and mentoring. Following the program, partners demonstrated a 90% improvement in their knowledge and skills related to identifying and managing tourism. This increase in capacity is expected to enhance the value of Baruttung Natural Bathing as a sustainable tourism destination, contributing to economic growth through job creation. Furthermore, this initiative aligns with government efforts to promote sustainable tourism development (SDGs 8) and supports the promotion of local culture and products (SDGs 12).